PRINSIP DASAR HUKUM ISLAM (Studi Terhadap fleksibilitas dan adabtabilitas hukum Islam) - Fatarib, HUsnul (JURNAL NIZHAM, 2014)
The longevity of a legal product is based on the truth of its core teaching, the users and the makers of that law. Islamic law is a product of syariah from Allah the human creator. Its core teaching is for the benefit of human being in the world and the after world. The slogan is reflected in the various principles of Islamic law both general principles and specific principles. These principles include the principle of tawhid, Justice, amar ma.ruf nahi mungkar, freedom, equality, and the ta.awun principles. Those principles exceed the principles from other law so that the existance of Islamic law should be defended for it is suitable with the modern life enthusiasm. If there is any who states that the syariah law is old-fashioned or syariah law can.t lead human to the happiness in life, the person ought to comprehend the principles of Islamic law so that he would acknowledge it. In this paper I shall briefly discuss how and what are the principles of Islamic law.Keywords: Principle, Islamic law, Perpetuity